PENERAPAN METODE OUTDOOR LEARNING UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN PJOK KELAS IV SDN 2 LOKTABAT SELATAN - Maris, Rizky Syawaldi; Rahmadi; Fakhrudin; Sujarwoko; Fani Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low active involvement of students in Physical Education, Sports, and Health (PJOK) learning due to the dominance of conventional approaches is the background of this study. The study aims to analyze the effectiveness of the implementation of the Outdoor Learning method in increasing the learning activity of grade IV students of SDN 2 South Loktabat. The method used was Classroom Action Research (PTK) of the Kemmis and McTaggart spiral model, carried out in two cycles with 28 students' research subjects. Data collection is carried out through structured observation and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed a progressive increase in each cycle: the percentage of pre-cycle completion was only 51.66% (average 14.64), increased to 64.29% in cycle I (average 18.00), and reached 89.54% in cycle II (average 25.07) with all students declared complete. These findings confirm that the Outdoor Learning method is able to create a learning ecosystem that is more contextual, interactive, and student-centered, thereby encouraging active involvement in the cognitive, affective, and psychomotor dimensions. This method is recommended as an alternative to innovative learning strategies in PJOK subjects at the elementary school level.